Promoting content variety in MOOCs: increasing learning outcomes with podcasts - Köhler, Daniel; Serth, Sebastian; Meinel, Christoph (Frontiers in Education, 2024)
Online education has become an integral part of everyday life. As one form of online education, traditional Massive Open Online Courses (MOOCs) mostly rely on video-based learning materials.To enhance accessibility and provide more variety of the learning content, we studied how podcasts can be integrated into online courses. Throughout three studies, we investigated the acceptance and impact of podcasts made available to learners on the online education platform openHPI. We employed three different study methodologies: Post-test Only Control Group, One-Shot Case Study and Static-Group Comparison. In this manuscript, we provide reasoning behind our methodology decisions, the podcast design and it's structure of presentation. Building on the data we collected from the online education platform openHPI, on which the studies have been performed with more than 5,000 learners, we derive podcasts as suitable addition to MOOCs. Findings from our first study indicate that podcasts prove similarly successful to videos in promoting educational content. Building on that, our second study derived an ideal podcast blueprint to be applied by fellow educators. Implementing the blueprint as weekly episodes alongside a six-week MOOC on cybersecurity with more than 1,500 learners, we identified that consuming an additional podcast can increase learning outcomes by up to 7.9%.